Rekaan Fesyen Wanita Secara "Reversible" Bertemakan Formal dan Kasual - Nor Rafidah, Kadir (Universiti Malaysia Sarawak, (UNIMAS), 2016)
The research is about women's fashion which includes some combination of garments such as jackets, blouses and skirts. The research also focused on the concept of women as a reversible fashion design with the themed of formal and casual. Reversible means something that can be changed and returned to its previous state, such as from front to back or from back to front. A simple silhouette design is used. The design concept is "serious to playful" which is geometrical and fruity.